Reported COVID-19 vaccines side effects among Algerian athletes: a comparison between inactivated virus, adenoviral vector, and mRNA COVID-19 vaccines - Oudjedi, A.; Allali, A.; Bekli, A.; Lounis, M.; Saad, H. B.; Boukoufa, M. (The Physician and Sportsmedicine, 2024)
Objectives Many types of COVID19 vaccines are administered globally, yet there is not much evidence regarding their side effects among athletes. This study evaluated the selfreported postvaccination side effects of inactivated virus, adenoviral vector, and mRNA COVID19 vaccines among Algerian athletes.